2008
DOI: 10.1248/cpb.56.1417
|View full text |Cite
|
Sign up to set email alerts
|

Lipophilicity Measurement of Drugs by Reversed Phase HPLC over Wide pH Range Using an Alkaline-Resistant Silica-Based Stationary Phase, XBridgeTM Shield RP18

Abstract: The lipophilicity of solutes, conventionally expressed by their partition coefficient in the 1-octanol/water system (log P oct ), is of high significance from both physicochemical and pharmacological viewpoints.1,2) A number of intermolecular forces between a solute and its environment (i.e., solvents) determine the partitioning process and its equilibration. In pharmacology, the forces are particularly important because they control the migration of solutes (drugs) to biomembranes. Not a few studies have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Nevertheless, in this work (performed on XBridge column) we found that either the number of H-donor and acceptor bonds does not improve the calibration and simple linear relationship is sufficient. Similar results were obtained by Liu et al [33], where it is shown that the retention on Xbridge column and partitioning in 1-octanol/water are controlled by the same balance of structural properties, namely van der Waals volume, H-bond acceptor basicity and dipolarity/polarizability. Thus, there seems to be a linear relationship between log k w and log P values on XBridge, making this column particularly suitable for the determination of lipophilicity by means of HPLC.…”
Section: Resultssupporting
confidence: 87%
“…Nevertheless, in this work (performed on XBridge column) we found that either the number of H-donor and acceptor bonds does not improve the calibration and simple linear relationship is sufficient. Similar results were obtained by Liu et al [33], where it is shown that the retention on Xbridge column and partitioning in 1-octanol/water are controlled by the same balance of structural properties, namely van der Waals volume, H-bond acceptor basicity and dipolarity/polarizability. Thus, there seems to be a linear relationship between log k w and log P values on XBridge, making this column particularly suitable for the determination of lipophilicity by means of HPLC.…”
Section: Resultssupporting
confidence: 87%
“…A comparison of observed retention times on C 18 -reverse-phase mass-chromatograms (a measure of hydrophobicity)51;52 with the potencies of the active compounds indicate a distinct deviation from the trend of 54 , suggesting specific and idiosyncratic effects, rather than bulk-effects (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…AQX‐MN115 was used as a control (Yang et al ., ; Andersen et al ., ). Lipophilicity measurements of the compounds were conducted as described (Liu et al ., ).…”
Section: Methodsmentioning
confidence: 97%